Kreativitas Guru Dalam Meningkatkan Hasil Belajar Peserta Didik - Mira Zulkifli; Danang Dwi Basuki (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2023)
Teacher creativity in learning is very influential on student understanding because the more creative the teacher is in delivering the material, the easier it is for students to understand the lesson and make students more creative in learning. Therefore, teachers must strive to find out student problems, beliefs and habits that can hinder progress and help improve learning outcomes through the creativity that teachers have to carry out this function, teachers must understand which are beneficial and not beneficial to students.